Intraorbital Cavernous Haemangioma (CHM) - Rahman, MS; Hossain, MA (Journal of Armed Forces Medical College, Bangladesh, 2010)
This is an interesting and rare case report of right intraorbital cavernous haemangioma near optic nerve of a 12 years boy who was hospitalized for right sided uniocular moderate axial proptosis and headache without any impairment of vision. Computed Tomographic (CT) scan showed fusiform enlargement of around right optic nerve just behind the eye ball. The mass was removed by right fronto-orbito-zygomatotomy incision and diagnosed post-operatively as intraorbital cavernous haemangioma (CHM). Key words: Intraorbital cavernous haemangioma. DOI: 10.3329/jafmc.v6i1.5990 Journal of Armed Forces Medical College, Bangladesh Vol.6(1) 2010 p.32-33